Factors Affecting Consumer Buying Behavior for Smartphones in Pune City - Ruchira Kulkarni (International Journal of Advanced Science and Technology, 2020)
The objective of this study was to find out leading factors which affects consumer buying behavior. Various studies have been done on factors influencing consumer buying behavior and purchase decision but very few were conducted in Pune city. The descriptive research design was used to conduct this study. Primary data was collected for this study by distributing structured questionnaire among smartphone users in Pune onto which factor analysis, Garrett ranking test, Chi-square tests have been carried out to generate a more precise analysis of buying behavior of consumers. Findings of the study shows “Price” is the lead factor which affects consumer by behavior followed by “Smartphone Features”, “Brand Elements”, “Social influence”. Also, the components which play important in consumer buying behavior are Next Generation, Reviews of Service, Points of difference, Advertising impact on peer-group, Brand perception by family and Endorsement. This study will not only help smartphone manufactures to understand how and what drives consumers to buy a smartphone but also to formulate better marketing and selling strategies. This study will also help telecom managers & smartphone manufacturers to understand smartphone requirements of consumers so that they can align their product design accordingly. The scope of this research was limited to smartphone users in Pune. This can be enhanced to a broader region as consumer behavior might show variations across regions.